Multiple linear regression modelling of hot water extraction of soursop juice - Quek, Meei Chien; Chin, Nyuk Ling; Yusof, Yus Aniza (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The effect of hot water extraction on juice yield, ascorbic acid, lightness and total soluble solids of soursop juice was modelled using the response surface methodology. The soursop samples were treated at extraction temperatures of 30, 60 or 90 °C for extraction times of 30, 90 or 150 minutes. The regression model adequately represented the experimental data with goodness of fit of R2 greater than 0.60. The juice yield (p<0.05), ascorbic acid (p<0.05), lightness (p<0.05) and total soluble solids (p<0.001) were significantly affected by extraction temperature. The juice yield, ascorbic acid and total soluble solids of soursop juice increased while lightness decreased with increasing extraction temperature.